Spiritual and Value-Based Islamic Educational Leadership in Indonesia: A Hermeneutic Inquiry into Love, Moderation, and Institutional Management - Mona Novita; Teten Jalaludin Hayat; Najiburrohman Najiburrohman; Abu Hasan Agus R; Hefniy Hefniy (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
This study proposes a conceptual framework that articulates the philosophical resonance between the spiritual-ethical teachings of Tanbih by Sheik Abdullah Mubarok a foundational text of the Qadiriyyah–Naqshabandiyyah Suryalaya tradition and Indonesia’s Love-Based Curriculum (Kurikulum Berbasis Cinta, KBC), a recent policy initiative of the Ministry of Religious Affairs, in shaping spiritual and value-based Islamic educational leadership. Drawing on philosophical hermeneutics (Gadamer), the research conducts a comparative interpretive analysis of these two texts to examine how the values of divine love (maḥabbah) and moderation (wasaṭiyyah/tawāzun) inform leadership orientation, ethical authority, and institutional direction within Islamic educational settings. The analysis identifies four interrelated dimensions of educational leadership: (1) an ontological foundation of leadership grounded in relational unity through divine love; (2) an ethical framework that reconciles spiritual integrity and civic responsibility through balance and moderation; (3) a compassionate pedagogical leadership approach that deepens the KBC’s “connection before correction” principle through the Sufi discipline of adab; and (4) a service-oriented leadership orientation rooted in rendah babarengan (humility in togetherness), re-envisioned as institutional khidmah. This study contributes to the field of Islamic Educational Leadership and Management by reframing leadership not merely as administrative control, but as a spiritually grounded, value-based practice that integrates ethical governance, compassionate pedagogy, and institutional responsibility. While the framework is conceptual and untested empirically, it offers a hermeneutically grounded theoretical foundation for future action research and case studies in madrasahs and other Islamic educational institutions. The study further invites scholarly inquiry into how locally rooted spiritual epistemologies can inform contemporary educational leadership and policy without being reduced to instrumental or bureaucratic functions.